Accuracy of autonomic symptoms in detection of severe cardiac autonomic neuropathy (Bangabandhu Sheikh Mujib Medical University Journal, 2022)
Autonomic neuropathy is a troublesome complication of diabetes mellitus often is not addressed by the physicians. The aim was to see the accuracy of autonomic symptoms in the detection of severe cardiac autonomic neuropathy (CAN). This study was done in BIRDEM in 62 adult patients with type 2 diabetes mellitus and cardiac autonomic neuropathy. Cardiac autonomic neuropathy was detected clinically by heart rate and blood pressure change to maneuvers such as deep breathing, valsalva and standing. Eight symptoms of autonomic neuropathy, namely exercise intolerance, dizziness, dysphagia, abdominal bloating, constipa- tion, diarrhea, gustatory sweating and impotence were tested. In this study, impotence was the most common symptom (58%). There was no difference in the frequency of autonomic symptoms between severe and non-severe cardiac autonomic neuropathy. Taking clinical tests as gold standard, gustatory sweating had the highest specificity (96%) and constipation had the highest sensitivity (54.05%) in detection of severe cardiac autonomic neuropathy. Sensitivity increased to 78.37 when a constellation of symptoms were tested. Autonomic symptoms are common in patients with type 2 diabetes and cardiac autonomic neuropathy. Collection of symptoms was associated with a high sensitivity for detection of severe cardiac autonomic neuropathy.BSMMU J 2022; 15(1): 11-15